PENERAPAN DIGITAL MARKETING MELALUI TEKNIK COPYWRITING DAN SEO BAGI UMKM - Dicky Supriatna; Julisar Surjadi; Deasy Ariyanti Rahayuningsih (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2022)
In today's technological era, digital marketing is one of the keys to business success. The implementation of digital marketing includes copywriting and Search Engine Optimization (SEO) techniques. The implementation of this service activity provides training for MSME actors to know, understand, and be able to practice information technology for digital marketing activities. Starting from preliminary interviews with MSME managing partners, several main problems were identified in their business marketing, namely first, insight into digital marketing, second, techniques to increase online sales, third, increasing product reputation, and fourth, improving product packaging and presentation quality. According to the needs of the participants, this training explains digital marketing, as well as conveys two techniques in digital marketing, namely copywriting and Search Engine Optimization (SEO). The stages of implementing Community Service are first, knowledge of digital marketing, second, understanding of copywriting, and third, the practice of implementing SEO in the participants' online business. In the main activity of implementing SEO techniques, participants were trained to use the Google Keyword Planner analysis tool. This training uses lectures, tutorials, discussion, and practice methods. This service implementation activity was carried out during the pandemic so the delivery of training activity material was carried out using Zoom media. Evaluation of the results of the activities was carried out through question and answer with the participants. As a result of this activity, it is hoped that MSME participants have started to apply Search Engine Optimization techniques to run their businessesABSTRAK:Di era teknologi saat ini, pemasaran digital menjadi salah satu kunci keberhasilan bisnis. Penerapan pemasaran digital diantaranya melalui teknik copywriting dan Search Engine Optimization (SEO). Pelaksanaan kegiatan pengabdian ini memberikan pelatihan kepada para pelaku UMKM agar mengetahui, memahami, dan mampu mempraktekkan teknologi informasi untuk kegiatan pemasaran secara digital. Berawal dari wawancara pendahuluan terhadap mitra pengelola UMKM, teridentifikasi beberapa masalah utama dalam pemasaran bisnis mereka yakni pertama, wawasan tentang pemasaran digital, kedua, teknik menaikkan penjualan secara online, ketiga, menaikkan reputasi produk, dan keempat, meningkatkan kualitas kemasan dan penyajian produk. Sesuai kebutuhan peserta tersebut, pelatihan ini membekali penjelasan tentang digital marketing, serta menyampaikan dua teknik didalam digital marketing yaitu copywriting dan SEO. Tahapan pelaksanaan Pengabdian kepada Masyarakat yaitu pertama, pengetahuan tentang digital marketing, kedua, pemahaman copywriting, dan ketiga, praktik menerapkan SEO dalam bisnis online para peserta. Pada kegiatan utama penerapan teknik SEO, peserta dilatih untuk memanfaatkan alat bantu analisis Google Keyword Planner. Pelatihan ini menggunakan metode ceramah, tutorial, diskusi, dan praktik. Kegiatan pelaksanaan pengabdian ini dilakukan dalam masa pandemik sehingga penyampaian materi kegiatan pelatihan dilakukan dengan menggunakan media Zoom. Evaluasi hasil kegiatan dilakukan melalui tanya-jawab dengan peserta. Hasil dari kegiatan ini diharapkan para peserta UMKM sudah mulai menerapkan teknik Search Engine Optimization untuk menjalankan usaha mereka.